2019
DOI: 10.1007/s00213-018-5163-6
|View full text |Cite
|
Sign up to set email alerts
|

α5GABAA subunit-containing receptors and sweetened alcohol cue-induced reinstatement and active sweetened alcohol self-administration in male rats

Abstract: Rationale: GABA A receptors containing the α5 subunit (i.e., α5GABA A ) appear to be critically involved in the reinforcing and subjective effects of alcohol. Their role in alcohol relapse remains unknown.Objectives: Pharmacological approaches were used to probe the role of α5GABA A receptors in alcohol seeking induced by re-exposure to an sweetened alcohol-paired cue, as well as in alcohol +sucrose vs. sucrose self-administration. Methods:For reinstatement studies, rats were trained to self-administer alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…In Experiment 2, it was demonstrated that naltrexone facilitated the elimination of alcoholmaintained behavior when used in conjunction with alternative non-alcohol reinforcers. These results are consistent with previous demonstrations that naltrexone can reduce alcohol-maintained behavior while not significantly decreasing sucrose-maintained behavior (e.g., Chandler et al, 2019) and with its use as an FDA-approved pharmacotherapy for AUD. That this difference was only observed in the first Phase 2 session followed by the rapid elimination of alcohol-maintained behavior in all rats regardless of presession treatment, may be due to the reinforcement parameters used in this experiment.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In Experiment 2, it was demonstrated that naltrexone facilitated the elimination of alcoholmaintained behavior when used in conjunction with alternative non-alcohol reinforcers. These results are consistent with previous demonstrations that naltrexone can reduce alcohol-maintained behavior while not significantly decreasing sucrose-maintained behavior (e.g., Chandler et al, 2019) and with its use as an FDA-approved pharmacotherapy for AUD. That this difference was only observed in the first Phase 2 session followed by the rapid elimination of alcohol-maintained behavior in all rats regardless of presession treatment, may be due to the reinforcement parameters used in this experiment.…”
Section: Discussionsupporting
confidence: 92%
“…The results of Experiment 2 are in line with those of previous experiments in which it was demonstrated that naltrexone can suppress alcohol-maintained behavior and mitigate its relapse (Chandler et al, 2019; Czachowski & Delory, 2009; Lê et al, 1999; Williams & Schimmel, 2008). These results also extend the resurgence literature by further demonstrating that resurgence can be affected by the presession delivery of drugs (Pyszczynski & Shahan, 2014; Quick et al, 2011).…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations